Genetic analysis of yield and yield contributing traits in rice (Oryza sativa L.) BC2F3 population derived from MR264 × PS2 - Hasan, Nor’aishah; Rafii, Mohd Yusop; Harun, Abdul Rahim; Alı, Nusaibah Syed; Mazlan, Norida; Abdullah, Shamsiah (Taylor & Francis, 2022)
High yield potential in rice is indirectly determined by yield-related traits. These traits are complex and regulated by several genes whose expression is affected by environmental conditions. It is of great importance to disclose the genetic relationships between yield and its yield components for multi-trait improvement in rice. Therefore, the present study aimed to investigate the genetic variability and inheritance patterns of yield and yield attributed traits in BC2F3 rice lines to identify the ideal lines from the selection. A total of 36 improved versions of blast resistant plants in the BC2F3 population used in this study were developed from a single cross between a high yielding mutant rice variety but susceptible to blast, MR264, and Malaysian local variety donor for Pi-7(t) and Pikh blast resistant genes. Analysis of variance showed that all traits were significantly different for lines except grain length and grain width. High heritability and genetic advance were recorded for plant height, number of tillers, filled grain, 1000-grain weight and seed setting rate. A significant and positive correlation was recorded with most evaluated traits, except for grain length and grain width. Thirty-six BC2F3 lines were clustered into four major groups and the first three principal components (PC3) contributed 71.13% of the total variation, with 1000-seed weight, yield/hill and filled grain being the main discriminatory characters. There was an adequate genetic variability in the lines, and 1000-grain weight, yield/hill and filled grain traits could be considered for indirect selection in breeding programs in next generations.